‘-(으)ㄹ 거예요’ VS ‘-(으)ㄹ게요’ DIFFERENCES IN KOREAN - Yunusova Gulshoda Dilshadovna; Mirjamilova Sevinch Mirjamilovna (Journals Park Publishing, 2023)
Korean has a number of future tense suffixes, and they differ depending on the field of use. This article compares the grammars of ‘-(으)ㄹ 거예요’ -(eu)l geoyeyo and ‘(으)ㄹ게요’ -(eu)lgeyo. The difference between them is explained. It is analyzed with the help of examples.
Keywords: future tense, ‘-(으)ㄹ 거예요’ -(eu)l geoyeyo, ‘(으)ㄹ게요’ -(eu)lgeyo, difference.